البعد الاجتماعي في رواية "من يستأجر لي وطنا " للطاهر مرابعي - عياشي عمر, إيمان; فريجات, ثورية; حميدة, ريان; بوزقاق, عصماء (University of Eloued جامعة الوادي, 2024)
تهدف الدراسة الموسومة بـــ البعد الاجتماعي في يستأجر لي وطنا؟ للطاهر إلى الكشف عن حيثيات الواقع المعيش للمغترب الجزائري، من خلال تمثلات الشخصيات السردية البارزة (زهير، سلاف، أحمد، عمي صالح)، والنظر في تبعات وأثار الفضاء المغترب إليه عليهم. وقد توصلنا إلى نتائج مهمة إلا أن أهمها: تجلى البعد الاجتماعي في الحديث عن معاناة الشاب الجزائري مع الأوضاع المادية الصعبة من خلال الشخصية الرئيسية زهير الذي دفعته الظروف لمغادرة البلاد بحثا عن الاكتفاء الذاتي. The Study, tagged "The Social Dimension", aims to rent a house for me? Al-Taher sought to reveal aspects of the living reality of the Algerian expatriate, through the representations of significant narrative characters (Zuhair, Sulaf, Ahmed, Ammi Saleh), and to consider the consequences and effects of the expatriate space on them, We have reached important results, but the most important of them is: The social dimension was evident in talking about the suffering of the Algerian young man with difficult financial conditions through the main character Zuhair, who pushed him conditions of leavingthe country in search of self-sufficiency.
دراسات أدبية